Conflictos mineros en el Perú: entre la protesta y la negociación - Paredes, Maritza (2019)
This article carries on an analytical review of literature on negotiation and mining conflicts, particularly in Peru. It also seeks to identify important theoretical recommendations offered by this literature.These recommendations serve to problematize future research on the challenges of these negotiation processes and their ability to overcome disagreements. Finally, based on these recommendations, the article presents and discusses the articles of the volume Extractive Industries, conflicts, negotiations and dialogues in Peru.